Physical Activity May Be Associated with Conditioned Pain Modulation in Women but Not Men among Healthy Individuals - Yukiko Shiro; Tatsunori Ikemoto; Yuta Terasawa; Young-Chang P. Arai; Kazuhiro Hayashi; Takahiro Ushida; Takako Matsubara (Pain Research and Management)
Background. Conditioned pain modulation (CPM), a phenomenon also known as diffuse noxious inhibitory control, is thought to be affected by various factors, including sex and level of physical activity. However, the involvement of these factors in CPM remains unclear. Methods. Eighty-six healthy young subjects (M/F, 43/43) participated in this study. Participants were assessed on the basis of their mechanical pressure pain threshold (PPT), CPM response, body mass index (BMI), basal metabolic rate (BMR), and duration of moderate-to-vigorous physical activity (MVPA) over a week, using a motion counter. Response to CPM was evaluated as PPT during painful cold stimulation relative to baseline PPT. Results. Men showed significantly higher baseline PPT than women; however, this difference was no longer significant after controlling for confounders. Stepwise multiple linear regression analyses revealed BMR to be a significant contributor towards baseline PPT in the entire study population. In contrast, although there were no significant contributors to CPM response among men and in the overall study group, MVPA was positively associated with CPM response among women (β = 0.397). Conclusions. These results suggest that, among healthy young individuals, CPM response may be associated with moderate-to-vigorous physical activity in women but not in men.